Pasar Seni Di Pekanbaru Dengan Pendekatan Arsitektur Melayu Riau - T.Nadhilah Putri; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The design of art marketplace in Pekanbaru is meant to fulfill of buying and selling activities of signature handicrafts and culinary of Riau. This design purpose to the sale and purchase of handicrafts, traditional snacks and souvenirs, the promotion of signature handicrafts and culinary of Riau, and also workshop of Riau’s handicraft such as Siak weaving, embroidery, tekat embroidery, woven, Riau batik, and wood craft , so visitors can see and try the process of making signature handicrafts of Riau. The Art Marketplace uses the design transformation method. This design uses the approach of Riau Malay Architecture. The Riau Malay Architecture Approach is taken from theMalay houses of four major rivers in Riau, that is Kampar River, Siak River, Rokan River, and Indragiri River, that will be transformed into the art marketplace buildings. The concept of designing the art marketplace is Harmony of Cultural Heritage. The concept of harmony is applied through therelationship of building orientation to the site and the relationship between buildings in the art marketplace. While the concept of cultural heritage applied to the transformation of Malay houses from four major rivers in Riau into the art marketplace buildings. The Main Building applies the transformation from the building of Isatan Rokan IV Koto. The Culinary Building applies the transformation from Rumah Lontiok, Kampar. The Workshop building applies the transformation from Balai Kerapatan Tinggi, Siak. The Handicraft Retail building applies transformation from Rumah Godang Suku Peliang, Koto Sentajo, Kuantan Singingi.Keywords: Art Marketplace, Handicraft, Culinary, Riau Malay Architecture, Harmony of Cultural Heritage.